1953
DOI: 10.1021/ja01097a057
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Borohydride, Its Hydrolysis and its Use as a Reducing Agent and in the Generation of Hydrogen1

Abstract: Sodium borohydride reacts slowly with water ultimately to liberate 4 moles of hydrogen per mole of the compound at room temperature, or 2.4 1. per gram. The reaction is greatly accelerated by rise of temperature or by the addition of acidic substances, for which latter purpose boric oxide is convenient and effective when the objective is the generation of hydrogen. Particularly striking is the catalytic effect of certain metal salts, especially that of eobalt(II) chloride. Thus pellets of sodium borohydride co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
548
1
9

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,043 publications
(593 citation statements)
references
References 0 publications
13
548
1
9
Order By: Relevance
“…Reproduced with permission from reference 3. First-principles calculations of the electronic structures of M(BH 4 ) n show that they are nonmetallic and have relatively large energy gaps of 1.8 4 ) n have been used as "one-way" hydrogen sources that release the hydrogen on contact with water (via hydrolysis) [9][10][11]. Because the hydrolysis reaction is highly irreversible, such materials are certainly not candidates for reversible hydrogen storage.…”
Section: Open Accessmentioning
confidence: 99%
“…Reproduced with permission from reference 3. First-principles calculations of the electronic structures of M(BH 4 ) n show that they are nonmetallic and have relatively large energy gaps of 1.8 4 ) n have been used as "one-way" hydrogen sources that release the hydrogen on contact with water (via hydrolysis) [9][10][11]. Because the hydrolysis reaction is highly irreversible, such materials are certainly not candidates for reversible hydrogen storage.…”
Section: Open Accessmentioning
confidence: 99%
“…[4] Although the reactions with water are usually fast, the reaction kinetics under practical conditions is rather slow, thus suggesting the use of expensive catalysts. [5] Catalytically accelerated NaBH 4 hydrolysis for the generation of hydrogen has been studied since the 1950s, [6] and it is now under intensive investigation, [5] leading to a number of recent applications. [7] However, until now, there is no experimental structural information on intermediate phases or reaction pathways in the NaBH 4 + H 2 O system.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1950s, Schlesinger et al [7] had first found that cobalt chloride could accelerate the decomposition of NaBH 4 in water. It is interesting that cobalt chlorides react with NaBH 4 , release H 2 and produce precipitate as byproduct; and the precipitate can help getting much faster hydrogen generation rates in the succeeding hydrogen generation reactions.…”
Section: Introductionmentioning
confidence: 99%